Spondylolysis in adolescent swimmers - Tatsumara, M.; Uchida, T.; Tsukagoshi, Y. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Low back pain has become one of the most common complaints among swimmers. Two primary causes of low back pain in adolescent athletes are disc degeneration and lumbar spondylolysis. Although there are some reports on disc degeneration in swimmers, there are few case reports on spondylolysis. Here, we report on five adolescent swimmers with low back pain that was diagnosed as spondylolysis. These included one freestyle, one backstroke, two butterfly stroke, and one breaststroke swimmers. At the first visit, two swimmers had pseudarthrosis that was incurable; therefore, conservative therapy for low back pain was started. The other three swimmers, in whom bone healing was expected, were asked to discontinue swimming and wear semi-hard braces. After several months` treatment, one swimmer had successful healing. The remaining two had failed healing and developed pseudarthrosis; hence, they were treated for low back pain. Lumbar spondylolysis refers to fatigue fracture of the pars interarticularis on the lumbar vertebrae arc that occurs frequently in athletes. It is caused by the repetition of extension and rotation of the lumbar spine. Although it can be easily diagnosed by identifying bone marrow edema via magnetic resonance imaging, athletes rarely visit a doctor because of mild pain. Although healing rate for early-stage spondylolysis is §80%, achieving fusion becomes difficult when the condition has progressed, and surgery becomes necessary after reaching the stage of pseudarthrosis. If fusion fails in the early stage, spondylolysis with pseudarthrosis may progress to spondylolisthesis, which leads to sciatica in adulthood.